YOUTH ENTREPRENEURSHIP CONSULTING CONCEPT IN VOCATIONAL (VOCATION AND TECHNICAL) EDUCATION INSTITUTIONS (Innovative professional education, 2023)
The publication updates the importance of youth entrepreneurship as an important social segment for the reconstruction of the national economy of Ukraine in war and post-war times. The semantics and logical-content structure of the scientific notion "concept" have been specified. The author's concept of consulting on youth entrepreneurship in vocational (vocational and  technical) education institutions is substantiated, the leading idea of which is to understand the nature of this complex psychological and pedagogical process as a kind of strategy of timely and effective assistance to future specialists in starting their own business and adapting business to the circumstances of civilization. The strategic invariants of youth entrepreneurship consulting of vocational education students are positioned, taking into account the specifics of the specified branch of the education system of Ukraine.
Keywords: youth entrepreneurship, concept, vocational education, consulting on youth entrepreneurship